Habitat use and diet overlap of Blue Catfish and Channel Catfish populations in two northeastern Kansas reservoirs - Jackson, Kade N. (My University, 2025)
Blue Catfish Ictalurus furcatus have increasingly gained recognition as a recreationally valuable species resulting in widespread stocking throughout the midwestern and eastern United States. Successful establishment and proliferation of stocked populations prompts questions about their impacts on other species of management interest through competition and predation. Standardized surveys in Kansas reservoirs have revealed increasing abundance of Blue Catfish populations following stocking. We hypothesize that increasing abundance of Blue Catfish might increase competitive interactions with Channel Catfish Ictalurus punctatus because they possess similar morphologies, life histories, and feeding strategies. Acoustic telemetry and gastric lavage were used to quantify the spatial and temporal habitat and diet overlap of these species in two northeastern Kansas reservoirs in 2023 and 2024. Generalized linear models and multivariate ordination techniques revealed that each species had differing spatial distribution patterns (p <0.001) and, on average, Blue Catfish occurred in deeper water (6.84 m) than Channel Catfish (5.09 m; p=0.048). We detected similar movement patterns for both species based on detections on receivers upstream of the reservoirs. Stomach contents of both species were comprised of diverse prey, but Channel Catfish fed more frequently on crayfish (p =0.001) and terrestrial macroinvertebrates (p = 0.022). Season had a strong effect on stomach contents (p = 0.001) for both species because of the occurrence of spring hatches of Giant Burrowing Mayflies Hexagenia limbata and fish eggs produced by spawning Longnose Gar Lepisosteus osseus, followed by a shift to terrestrial macroinvertebrates (p = 0.001) in the fall. Both species exhibit the potential to use a broad range of habitat and dietary resources; however, under high abundances of Blue Catfish, our data suggests that Channel Catfish might shift resource use to minimize interspecific interactions. Monitoring is necessary to evaluate populations trends and inform harvest management to prevent Blue Catfish populations from negatively impacting their own population and abundance and other species.
Keywords: Blue catfish; Channel catfish; Habitat; Diet